2015
DOI: 10.1155/2015/853573
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Polymorphisms and Expression of Enzyme-Encoding Genes Related to Glutathione in Hematopoietic Cancers and Solid Tumors

Abstract: Antioxidant compounds such as glutathione and its enzymes have become the focus of attention of medical sciences. Glutathione, a specific tripeptide, is involved in many intercellular processes. The glutathione concentration is determined by the number of GAG repeats in gamma-glutamylcysteine synthetase. GAG polymorphisms are associated with an increased risk of schizophrenia, berylliosis, diabetes, lung cancer, and nasopharyngeal tumors. Cancer cells with high glutathione concentration are resistant to chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 57 publications
0
22
0
1
Order By: Relevance
“…Ki-67 protein is expressed during all active phases of the cell cycle (G 1 , S, G 2 , and mitosis), but is absent from resting cells (G 0 )32. GPX3 gene codes for the Glutathione peroxidase 3, also known as plasma glutathione peroxidase (GPx-P), the variations in activity of GPX1, GPX2, and GPX3 isoforms may be associated with the development of cancers, for example, prostate cancer or even colon cancer39. Leprecan-like 1 is a potential tumor suppressor gene since it has been demonstrated to be downregulated in the hepatocarcinoma tissues and its overexpression inhibits cancer cell proliferation and colony formation through regulation of the cell cycle by downregulation of cyclins40.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 protein is expressed during all active phases of the cell cycle (G 1 , S, G 2 , and mitosis), but is absent from resting cells (G 0 )32. GPX3 gene codes for the Glutathione peroxidase 3, also known as plasma glutathione peroxidase (GPx-P), the variations in activity of GPX1, GPX2, and GPX3 isoforms may be associated with the development of cancers, for example, prostate cancer or even colon cancer39. Leprecan-like 1 is a potential tumor suppressor gene since it has been demonstrated to be downregulated in the hepatocarcinoma tissues and its overexpression inhibits cancer cell proliferation and colony formation through regulation of the cell cycle by downregulation of cyclins40.…”
Section: Discussionmentioning
confidence: 99%
“…The GSTO-1 enzyme is responsible for catalyzing the reaction that results from glutathione conjugates generated by GSH in response to damage signals, thus influencing the relationship between reduced glutathione and oxidized glutathione (GSH/GSSG) modulating the expression of cytokines related to the Th1 immune response (Dobashi et al, 2001), thus playing a key role on the host immune response modulation. To date, very few studies have identified the effect of SNP into the gsto-1 sequence (He et al, 2013;Zmorzynski et al, 2015), including teleost species (Liao et al, 2017). The analysis of the four gsto-1 nonsynonymous SNPs found by SIFT and POLYPHEN showed two of them with the second (c.205A > G; c484T > C) and the highest (c.499T > C; c.769A > C) score possible.…”
Section: Discussionmentioning
confidence: 99%
“…There are many polymorphisms in the antioxidant enzymes' genes which may alter their ROS detoxification efficiency. It has been suggested that rs1050450 polymorphism of GPx‐1 gene (leucine for proline substitution in residue 198, in 3, 3p21 region) may affect GPx‐1 enzyme function . Moreover, the rs4880 polymorphism which is located on the second exon of SOD2 gene (6, 6q25 region) and is a functional polymorphism at the 16th amino acid of SOD2 (Val16Ala) could alter the enzyme conformation .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that rs1050450 polymorphism of GPx-1 gene (leucine for proline substitution in residue 198, in 3, 3p21 region) may affect GPx-1 enzyme function. 26 Moreover, the rs4880 polymorphism which is located on the second exon of SOD2 gene (6, 6q25 region) and is a functional polymorphism at the 16th amino acid of SOD2 (Val16Ala) could alter the enzyme conformation. 27 This substitution induces a 30-40% reduction in SOD2 antioxidant activity by the reduction of its transportation into the matrix of mitochondria.…”
Section: Discussionmentioning
confidence: 99%